The Star, 22 Julai 2008 - Bhag Singh (Star Publications, 2008)
There is much excitement over the listing of George Town and Malacca as Unesco World Heritage Sites. Going by reports, there will be a three-day celebration by Penangsites, while Malacca willa celebrate the event next month and perhaps on a grander scae